A Methodology for Fault Pre-Consolidation prior to Longwall Retreat: A Case Study from Kestrel Coal - Dion Pastars (International Conference on Ground Control in Mining, 2007)
Kestrel Coal has undertaken a surface-to-seam consolidation program of faulted ground prior to longwall retreat in the 304 panel. Micro fine cement is used to improve the rock mass quality and therefore reduce the risk to personnel and equipment whilst increasing previously assumed sterilised reserves. The program is based on information attained from previously successful grouting campaigns in the Queensland coal area and follows the decision making process to ensure there is sufficient spatial permeation of cement across the faulted area. This data is used to assess the residual risk to the business in terms of health, safety and production